How resilient is the German banking system to macroeconomic shocks? - Jonas Dovern; Carsten-Patrick Meier; Johannes Vilsmeier (Kiel Institute for the World Economy (IfW), 2008)
Macro-stress testing studies often rely on rather short sample periods due to the limited availability of banking data. They may fail to appropriately account for the cyclicality in the interaction between the banking system and macroeconomic developments. In this paper we use a newly constructed data set on German banks' income and loss statements over the past 36 years to model the interaction between the banking sector and the macroeconomy. Our identified-VAR analysis indicates that the level of stress in the banking sector is strongly affected by monetary policy shocks. The results rationalize the active behavior of central banks observed during periods of financial market crises.
Keywords: C32; E44; 330; Banking; VAR; Stress testing; Bankensystem; Finanzmarktkrise; Konjunktur; Schock; Geldpolitik; VAR-Modell; Deutschland